The oxidative stress of hyperglycemia and the inflammatory process in endothelial cells. - Muniandy, S.; Qvist, R.; Yan, G.O.S.; Bee, C.J.; Chu, Y.K.; Rayappan, A.V. (The University of Tokushima, Faculty of Medicine, 2009)
Hyperglycemia and insulin resistance are common in many critically ill patients. Hyperglycemia increases the production of reactive oxygen species in cells, stimulates the production of the potent proinflammatory cytokines IL-8 and TNF-alpha, and enhances the expression of haem oxygenase-1, an inducible stress protein. It has been shown that administration of insulin and the semi-essential amino acid glutamine have been beneficial to the septic patient. The aim of our study is to test whether these two molecules, glutamine and insulin used in combination attenuate the proinflammatory responses in endothelial cells which have been triggered by hyperglycaemia. Our results demonstrate that a combination of insulin and glutamine are significantly more effective in reducing the expression of IL-8, TNF-alpha and HO-1 than insulin or glutamine alone.